EURASIAN RESERVE SYSTEM: CONCERNING MECHANISM OF FINANCING SOCIALLY IMPORTANT INFRASTRUCTURAL ECOLOGICAL PROJECTS AND PROGRAMS - Vyacheslav I. Karpunin; Tatiana S. Novashina (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
The lake Baikal, as an object of the global nature heritage is facing an ecological disaster of the national scale. This is one of the most important conclusions drawn by the Baikal International Ecological Water Forum while discussing problems of preserving the ecosystem of the lake Baikal and rational use of its resources. In spite of serious attention on the part of federal and regional authorities to this problem, first of all by preparing, adopting and implementing the Water Strategy of the Russian Federation for the period up to 2020, the Principles of Ecological Policy of the Russian Federation and by efforts aimed at practical realization of important programs, such as the Federal program ‘Protection of the Lake Baikal and Social and Economic Development of the Baikal Natural Territory for 2012–2020’, the Federal program ‘The Development of the Water Industry of the Russian Federation in 2012–2020’ (the program ‘Water in Russia’), the problem of preserving the ecosystem of the lake Baikal is deteriorating and could reach the critical point. On the basis of the new concept of managing national wealth the article describes the Eurasian reserve system, an absolutely new form of financing, which differs from the current form, i.e. state-private partnership. The authors explain the concept and key structural elements of the new investment mechanism of financing socially important ecological projects and programs functioning on the basis of the reserve system and its essential component – regional mortgage funds of development. They assume that proposed investment mechanisms of financing infrastructural ecological projects and programs of developing water industry in Russia could decline considerably global resource risks and would ensure effective realization of the program ‘Protection of the Lake Baikal and Social and Economic Development of the Baikal Natural Territory for 2012–2020’, the program ‘The Development of the Water Industry of the Russian Federation in 2012–2020’ to reach prosperity of people in Russia and guarantee the development of economy in Russian regions.